2016
DOI: 10.3329/bjp.v11i2.26505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydro-alcoholic extract of <i>Ziziphus spina-christi</i> against scopolamine-induced anxiety in rats

Abstract: <p class="Abstract">The aim of this study was to observe the effect of <em>Ziziphus spina-christi</em> extract against anxiety related behavior induced by scopolamine. Rats were randomly divided into six groups, each group consists of eight rats. Vehicle group received distilled water, negative control received scopolamine (1 mg/kg) and positive control received diazepam (1 mg/mL). Experimental groups received <em>Z. spina-christi</em> extract (50, 100 and 200 mg/kg IP) 30 min aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The present work found that the effects of pretreatment with crude extract exhibited a remarkable gephyrin expression in brain tissues similar to those of diazepam group as compared to those of PTZ-kindled mice. The finding reinforced the sedative effect of Zizyphus spina christi leaf extract and it is in harmony with that of previous study (5) . This sedative nature of Zizyphus crude extract may be related to its peptide, cyclopeptide alkaloids, and saponin contents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present work found that the effects of pretreatment with crude extract exhibited a remarkable gephyrin expression in brain tissues similar to those of diazepam group as compared to those of PTZ-kindled mice. The finding reinforced the sedative effect of Zizyphus spina christi leaf extract and it is in harmony with that of previous study (5) . This sedative nature of Zizyphus crude extract may be related to its peptide, cyclopeptide alkaloids, and saponin contents.…”
Section: Discussionsupporting
confidence: 91%
“…PTZ originally acts as an antagonist on GABA receptor. Owing to presence of miscellaneous bioactive compounds such as alkaloids, flavonoids, steroids, phenols and saponins in Zizyphus spina christi (14,15) , it was disclosed that its extract possess diverse pharmacological effects against the brain disorders such as anti-anxiety effect (5) , attenuation of memory impairment induced via scopolamine (16) , and neuroprotection against cerebral ischemia (6) . The present work found that the effects of pretreatment with crude extract exhibited a remarkable gephyrin expression in brain tissues similar to those of diazepam group as compared to those of PTZ-kindled mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations provide evidence for the development of new agents with less adverse effects (Predictable SEAU, 2006). In the search for a novel drug product for the treatment of psychiatric illness, large number of medicinal plants such as Areca catechu (Dar and Khatoon, 1997), Capsicum annuum (Jawad et al, 2017), Crocus sativum (Hosseinzadeh and Noraei, 2009), Hypericum perforatum (Kumar et al, 2000), Melissa officinalis (Akhondzadeh et al, 2003), Morus alba (Yadav et al, 2008), Nigella sativa (Raza et al, 2007), and Ziziphus spina-christi (Setorki, 2016) have been investigated for their therapeutic potential in variety of animal models.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves contain phytosterols such as β-sitosterol, glycoside, flavonoids, saponins, tannins and lactone (Asgarpanah and Haghighat, 2012). Hydroalcoholic extract of Ziziphus spina-christi was found to be effective against scopolamine-induced anxiety in rats (Setorki, 2016). There is no previous study on the learning and memory-enhancing activities of Z. spina- …”
mentioning
confidence: 98%